Utility of the 2019 EULAR/ACR SLE classification criteria for predicting mortality and hospitalisation: development and cross-validation of ominosity score - Ali Duarte-García; Gabriel Figueroa-Parra; Andrew C Hanson; Cynthia Crowson; Kamil E Barbour; Alain Sanchez-Rodriguez; María C Cuéllar-Gutiérrez; Mariana González-Treviño; José A Meade-Aguilar (RMD Open)
Objective The 2019 European Alliance of Associations for Rheumatology (EULAR)/American College of Rheumatology (ACR) systemic lupus erythematosus (SLE) classification criteria score (≥20 points) has been associated with poor outcomes. We aimed to evaluate its utility as a predictor for mortality and hospitalisation and to derive and validate an ominosity score based on the SLE classification criteria set.Methods Incident patients with SLE in a population-based cohort were included. The association between the 2019 EULAR/ACR SLE score and mortality and hospitalisation was assessed using Cox regression adjusted for age, sex and calendar year. An ominosity score for mortality was developed based on the SLE criteria set. The least absolute shrinkage and selection operator method was used to estimate model coefficients. Concordance and calibration were assessed by cross-validation and by plotting the observed event rates against the deciles of predicted probabilities.Results Among 374 patients with incident SLE, a EULAR/ACR score ≥20 points was not associated with an increased risk of mortality (HR 1.17, 95% CI 0.67 to 2.03) or first hospitalisation (HR 1.14, 95% CI 0.79 to 1.64) compared with a score ≤19 points. The derived ominosity score for mortality included age, sex, thrombocytopaenia, neuropsychiatric manifestations, subacute cutaneous or discoid lupus, non-scarring alopecia, inflammatory arthritis, renal involvement, antiphospholipid antibodies and hypocomplementaemia. This model demonstrated a concordance=0.76 with adequate calibration. Age and sex were the main predictors, as seen in the model including just age, sex and year (concordance=0.77).Conclusion The 2019 EULAR/ACR SLE criteria score was not associated with mortality and hospitalisation. The derived ominosity score for mortality presented good prediction for mortality but was not better than age and sex alone.